1984
DOI: 10.1021/i200027a004
|View full text |Cite
|
Sign up to set email alerts
|

Polymer waste reclamation by pyrolysis in molten salts

Abstract: The rubber-rich organic fraction from an automobile shredder has been pyrolyzed in a variety of molten salts at temperatures between 380 and 570 °C. The reactions are very rapid. As the temperature Is Increased, the amount of methane Increases, while the C* gases decrease. Gas production was higher [30% (wt/feed)] with more acidic melts such as NaCI/AICI3. Production of lower boiling oils is favored by longer residence times In the reactor. Hydrogen Is the limiting factor In the reactions, the residue being a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 5 publications
1
10
1
Order By: Relevance
“…Residual solids, such as char and ash, are retained in molten salt for subsequent handy separation and disposal [2]. The potential benefits of molten salt for solar gasification were first demonstrated by Epstein [5], and subsequently investigated by several research groups [6][7][8][9][10][11][12][13]. Recently, the solar gasification of coal and activated carbon with CO 2 in molten salt has also been investigated [9,11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Residual solids, such as char and ash, are retained in molten salt for subsequent handy separation and disposal [2]. The potential benefits of molten salt for solar gasification were first demonstrated by Epstein [5], and subsequently investigated by several research groups [6][7][8][9][10][11][12][13]. Recently, the solar gasification of coal and activated carbon with CO 2 in molten salt has also been investigated [9,11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Molten salt instead of molten zinc may be used to pyrolyse tyres [17] . A major drawback of salt over zinc is that the rCB will be contaminated with salt [18] and, as a result, another unit operation to remove the salt from the rCB would be required. The zinc based process discussed in this paper has, therefore, a significant advantage over the salt based process.…”
Section: Additional Informationmentioning
confidence: 99%
“…The reason why copper (II) chloride possesses stronger degradation activity than the other catalysts can be explained based on previous research results. Chambers et al [12] have found a few molten salts, like copper (I) chloride, were active in polymer waste reclamation due to their excellent heat transfer properties. In addition, Schmitz et al [13] also reported that copper (II) chloride was active for methanol decomposition between 350 8C and 450 8C.…”
Section: Catalyst Screening For Pbt Degradationmentioning
confidence: 99%